Luminescent ﬂuorinated chiral liquid crystalline oligomers containing Eu(III) complexes. Issue 5 (9th April 2019) - Bing, Yao; Xihua, Du; Yan, Chen; Shifan, Wang; Jing, Li; Liming, Dong; Yuehua, Cong
ABSTRACT: Luminescent ﬂuorinated chiral liquid crystalline oligomers containing Eu(III) complexes (Eu-LCOs) with good liquid crystalline properties and obvious luminescence properties were prepared using Poly(methylhydrogeno)siloxane (PMHS), chiral liquid crystalline monomer (M1 ), ﬂuorinated liquid crystalline monomer (M2 ), ﬂuorinated Eu(III) complex (M3 ). The chemical structures, liquid crystalline behaviours of Eu-LCOs were characterised by various experimental techniques. The introduction of small quantity of ﬂuorinated Eu(III) complexes endowed the oligomers with excellent luminescence properties. The Eu(III) complexes did not change the liquid crystalline textures of the oligomers. Fourier transform infrared imaging showed that Eu(III) complexes were evenly distributed in oligomers. In order to express the mutual effect and distribution of the components, a structural representation of Eu-LCOs was established. The Eu-LCOs displayed wide mesophase temperature ranges and reversible mesomorphic phase transitions. The Eu-LCOs can emit soft red light when being excited. Luminescence intensities of Eu-LCOs gradually increased with an increase of Eu(III) complexes from 0 to 1.0 mol%. However, the luminescence intensities of Eu-LCOs decreased monotonically with the increase of temperature in liquid crystalline phase. Graphical Abstract: